(untitled) (Journal of Asian Development Studies, 2013)
The prime focus of the study was to find out causal relationship between per capita GDP and per capita electricity consumption for Pakistan using cointegration and granger causality analyses. This study covers time series data from 1971 to 2010 for both of variables. Unit root analyses reveals that both variables are stationary of same order. Cointegration analyses confirm long run associationship between per capita electricity consumption and per capita GDP. Causal relationship was confirmed using Granger causality test which reveals unidirectional causality flowing from electricity consumption to economic growth. Variance decomposition test confirms that in duration of 10 years up to 14% variations in GDP are brought by electricity consumption. The result reveals that for developing countries like Pakistan important policies should be adopted and applied for enhancing electricity sector especially by focusing on hydroelectricity. So if electricity sector improves it will further stimulate the economic growth of Pakistan.